BEPS – A challenge for the increasing budget revenues in the process of digitalization - Ionuț MIȘA (Theoretical and Applied Economics, 2020)

(untitled)
In this paper we analyze the measures that led to the formation and implementation of the action plan regarding the outsourcing profit. These measures are adopted in the European Union and are also found in the Romanian tax code starting with 2018. The analysis is based on the action number 1 – “Digital Economy”. In the end, we will analyze the strategy that is based on the CCCTB (Common Consolidated Corporate Tax Base).